Word Counts? Considering National Systems of Accountability and Assessment in Adult Literacy and Numeracy - Ralf St.Clair; Aliza Belzer (Adult Education Research Conference, 2007)
Analysis of three national systems of accountability in ABE gives rise to significant insights for instruction, assessment, and policy in adult education.